PERSEPSI MASYARAKAT TERHADAP UNSUR-UNSUR MAGIC DALAM TRADISI PACU JALUR DI DESA SAWAH KECAMATAN KUANTAN TENGAH KABPATEN KUANTAN SINGINGI - Rena Audia; Gimin Gimin; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the persistence of magic elements inthis Pacu jalur activity which is closely related to the level of understanding of societywith the religion they profess, that is Islam. The public believes this is not wrong withIslamic teachings. Because they also use Islamic sayings. It’s on this basis this activityhas survived and continues to this day. The purpose of this study was to determinepeople's perceptions of magic elements in the pacu Jalur tradition. Data collectiontechniques in this study were observation, interviews and documentation. TheRespondents of this research were seven people, are: one of dukun jalur, one oftraditional community leader, one of jalur committee, two of racing children and twopeople from Sawah Village, consisting of indigenous and immigrant communities. dataanalysis techniques in this research used qualitative methods. The result of thisresearch is that people believe in this magic because it has become a hereditary andmagical tradition that is very much needed in the pacu jalur tradition. This magicalelement is considered very important, especially to keep the track and the race fromunwanted things and to gain victory. There are people who consider magic to be wrongwith the teachings of Islam and there are also some who say they are not wrong withIslam.Key Words: Magic elements, Tradition, Pacu Jalur